Analisis Kesalahan Berbahasa Bidang Morfologi Pada Teks Ulasan Siswa Kelas VII MTs N 1 Boyolali Tahun Ajaran 2024/2025 - Puspasary, Al Qony; Adtya, Rizal Friska; Purwanti, Diya Ika (STKIP PGRI Ponorogo Press, 2024)
The aim of this research is to find out how many language errors in the field of morphology are made in the explanation texts made by class VII students at MTs N 1 Boyolali for the 2024/2025 academic year. This research is a qualitative study that focuses on the analysis of language errors in the field of morphology in the review texts of class VII students at MTs N 1 Boyolali for the 2024/2025 academic year. Qualitative descriptive method, this research identifies and analyzes mistakes made by students in the field of morphology, especially in writing review texts. Data was collected through literature study of student worksheets, which were then analyzed in depth to find patterns of errors that occurred. The results of the research revealed that there were various language errors in the field of morphology made by students in writing review texts. These errors include errors in the use of prefixes, suffixes, confixes, and reduplication. Some examples of errors found include the use of inappropriate prefixes such as appreciate, tail, oblige, happy, and so. Apart from that, there are also errors in the use of suffixes such as place and complaint, as well as errors in the use of suffixes such as hard and so. In fact, it was also found that words were used that were considered reduplication even though they were not, such as in vain and repeatedly.